The Influence of the Stimulus Design on the Harmonic Components of the Steady-State Visual Evoked Potential - Solf, Benjamin; Schramm, Stefan; Blum, Maren-Christina; Klee, Sascha (Frontiers in Human Neuroscience, 2020)
Steady-state visual evoked potentials (ssVEPs) are commonly used for functional objective diagnostics. In general, the main response at the stimulation frequency is used. However, some studies reported the main response at the second harmonic of the stimulation frequency. The aim of our study was to analyze the influence of the stimulus design on the harmonic components of ssVEPs. We studied 22 subjects (8 males, mean age ± SD = 27 ± 4.8 years) using a circular layout (r1 = 0–1.6°, r2 = 1.6–3.5°, r3 = 3.5–6.4°, r4 = 6.4–10.9°, and r5 = 10.9–18°). At a given eccentricity, the stimulus was presented according to a 7.5 Hz square wave with 50% duty cycle. To analyze the influence of the stimulus eccentricity, a background luminance of 30 cd/m2 was added to suppress foveal stray light effects; to analyze the influence of simultaneous foveal and peripheral stimulations, stimulations are performed without stray light suppression. For statistical analysis, medians M of the amplitude ratios for amplitudes at the second harmonic to the first harmonic and the probability of the occurrence of the main response at the second harmonic P(MCSH) are calculated. For stimulations with foveal stray light suppression, the medians were M0–1.6° = 0.45, M1.6–3.5° = 0.45, M3.5–6.4° = 0.76, M6.4–10.9° = 0.72, and M10.9–18° = 0.48, and the probabilities were P0–1.6°(MCSH) = 0.05, P1.6–3.5°(MCSH) = 0.05, P3.5–6.4°(MCSH) = 0.32, P6.4–10.9°(MCSH) = 0.29, and P10.9–18°(MCSH) = 0.30. For stimulations without foveal stray light suppression, the medians M were M0–1.6° = 0.29, M1.6–3.5° = 0.37, M3.5–6.4° = 0.98, M6.4–10.9° = 1.08, and M10.9–18° = 1.24, and the probabilities were P0–1.6°(MCSH) = 0.09, P1.6–3.5°(MCSH) = 0.05, P3.5–6.4°(MCSH) = 0.50, P6.4–10.9°(MCSH) = 0.55, and P10.9–18°(MCSH) = 0.55. In conclusion, the stimulus design has an influence on the harmonic components of ssVEPs. An increase in stimulation eccentricity during extrafoveal stimulation leads to a transition of the main response to the second harmonic. The effect is enhanced by a simultaneous foveal stimulation.